Inspection No.1 and No.2 of Postal Obligations Concerning Mail Parcels under Eu-Regulated Universal Services - Ercsey, Ida (Communications - Scientific letters of the University of Zilina, 1999)
The examination of the possibility of the nation-wide delivery of postal packets no larger than 10 kg. The comparison of the present and expected packet service level. The presentation of the new packet forwarding service and the conditions for its introduction. The putting into figures of the extra turnover at the distribution points and of the transportation tasks in the new packet delivery system. Cost calculation for the service according to the EU regulations.